2016
DOI: 10.15376/biores.11.3.6920-6931
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Electroless Copper Plating on Poplar Veneer

Abstract: Copper coating was deposited on poplar veneer using different relative concentrations of plating solution. The coating structure, thickness, crystal structure, surface resistivity, contact angle, surface free energy, and electromagnetic shielding effectiveness were investigated. The surface morphology and thickness were observed using scanning electron microscopy, and the crystal structure was analyzed using X-ray diffraction. Increasing the relative concentration of plating solution resulted in a uniform and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…After two electroless runs, the EMI shielding effectiveness of wood veneer improved considerably, and the attenuation of shielding effectiveness was limited as electromagnetic wave frequency increased. The electromagnetic shielding performance is not lower than 45 dB in frequencies ranging from 10 MHz to 1.5 GHz., which is close to related literature (Guo 2016). However, as improvement in EMI shielding effectiveness was limited beyond two electroless runs, electroless runs were sufficient to achieve effective EMI shielding.…”
Section: Emi Shielding Effectivenesssupporting
confidence: 86%
See 1 more Smart Citation
“…After two electroless runs, the EMI shielding effectiveness of wood veneer improved considerably, and the attenuation of shielding effectiveness was limited as electromagnetic wave frequency increased. The electromagnetic shielding performance is not lower than 45 dB in frequencies ranging from 10 MHz to 1.5 GHz., which is close to related literature (Guo 2016). However, as improvement in EMI shielding effectiveness was limited beyond two electroless runs, electroless runs were sufficient to achieve effective EMI shielding.…”
Section: Emi Shielding Effectivenesssupporting
confidence: 86%
“…Finally, for conductive metal-type electromagnetic shielding materials, the key to electromagnetic shielding performance is the continuity of the metal layer rather than the thickness of the metal. Therefore, it is replaced by metal aluminum foil because of its low cost and flexibility (Guo et al 2016;Zhou and Zhao 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The crystal patterns of the samples were obtained by electroless Ni once before electroless plating Cu twice and electroless Cu two times before electroless Ni one time deposition. Figure 4a showed that the diffraction peaks at 2θ = 43, 50.54 and 74.44° were facecentered cubic structures Cu (111), ( 200) and (220), respectively [19]. The diffraction peak at 2θ = 44.5°w as the characteristic peak of the face-centered cubic structure Ni (111) [20];In Fig.…”
Section: Xrd Analysismentioning
confidence: 91%
“…The composite coatings exhibited the optimal shielding performance (average 90.69 dB) in the L-band ranged from 300 kHz to 2.0 GHz, which demonstrated that the maximum value (electromagnetic shielding effectiveness) was up to 100 dB and the electromagnetic shielding effectiveness was very stable. The electromagnetic shielding effectiveness of the Cu coatings-based wood was only 62 dB ranging from 10 kHz to 1.5 GHz [39,40]. The emerged synergistic effect of Cu and Ni coatings on electromagnetic shielding performance originated from two features of composite coatings-based segregated conductive networks [41,42] and specific interfacial polarization.…”
Section: Electromagnetic Shielding Effectivenessmentioning
confidence: 99%